Nutritional practice of pregnant women in Buno Bedele zone, Ethiopia: a community based cross-sectional study - Worke Sisay Yismaw; Tigist Shayi Teklu (BMC, 2022)
Plain Language Summary Worthy health and welfare is part of the goals set by united nation. Dietary practice is visible activities or conducts of eating habit performed by a person. To have healthy and appropriate working of the body, eating balanced diet is very crucial. This study found that about 185 (31.2%) pregnant mothers had good dietary practice. The mothers' educational status, income, dietary knowledge and pregnancy intervals were factors found to be affecting the nutritional practices of pregnant women. The finding indicated that the majority of study participants had a poor dietary practice, which is a concern because having poor dietary practice contributes to maternal and neonatal mortality and morbidity. To avert the problem this results healthy pregnancy. We need to focus on; nutrition education on basic nutrients, community mobilization on a diet using media, work on barriers and advocating nutrition practice.